RESISTANCE COMPONENT ANALYSIS OF TRADITIONAL FISHING BOAT IN CILACAP - S Samuel (Jurnal Kelautan, 2016)
RESISTANCE COMPONENT ANALYSIS OF TRADITIONAL FISHING BOAT IN CILACAPMonohull fishing boats used to catch fish is modified into a catamaran boat. The purpose of this modification is to get more fish. Catamaran ship has a double hull, but with the double hull ships resulted in increasingly complex resistances. It is interesting to study in depth about the resistance components of Catamaran boat. Resistance Components not only consist of surge resistance, frictional resistance, and the form resistance but with the distance between demihull causing interference waves. There are many research results of Catamaran boat in that aspect, but the data and information obtained from the experiment is still inadequate. In addition, there is still lack of accuracy particularly in predicting interference resistance component in calm water (calm-water resistance) as a result of the distance between the demihull. This study aims to describe the resistance component at Catamaran boat by using slender body method. Keywords: catamaran, Cilacap, slender body method ABSTRAK Kapal ikan monohull yang biasa digunakan untuk mencari ikan dimodifikasi menjadi kapal catamaran. Tujuan modifikasi ini untuk mendapatkan muatan ikan yang lebih banyak. Kapal Catamaran mempunyai dua lambung, tetapi dengan adanya dua lambung mengakibatkan hambatan kapal semakin kompleks. Menarik untuk dikaji lebih lanjut tentang komponen hambatan kapal Catamaran. Komponen hambatan tidak hanya terdiri dari hambatan gelombang, hambatan gesek, dan hambatan bentuk namun dengan adanya jarak antar demihull sehingga menimbulkan interferensi gelombang. Sudah banyak dijumpai hasil riset kapal Catamaran pada aspek tersebut, tetapi data dan informasi yang diperoleh dari eksperimen masih kurang memadai. Disamping itu, masih ditemukan ketidak-akurasian khususnya dalam memprediksi interferensi komponen hambatan pada air tenang (calm-water resistance) akibat dari adanya jarak antar demihull tersebut. Penelitian ini bertujuan untuk memaparkan komponen hambatan pada kapal Catamaran dengan menggunakan slender body method.  Kata kunci: catamaran, Cilacap, slender body method